2004
DOI: 10.1021/ic049532x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Ferriheme Reduction by Nitric Oxide:  Nitrite and General Base Catalysis1

Abstract: The reductive nitrosylation (Fe(III)(P) + 2NO + H(2)O = Fe(II)(P)(NO) + NO(2)(-) + 2H(+)) of the ferriheme model Fe(III)(TPPS) (TPPS = tetra(4-sulfonatophenyl)porphyrinato) has been investigated in moderately acidic solution. In the absence of added or adventitious nitrite, this reaction displays general base catalysis with several buffers in aqueous solutions. It was also found that the nitrite ion, NO(2)(-), is a catalyst for this reaction. Similar nitrite catalysis was demonstrated for another ferriheme mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
124
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(137 citation statements)
references
References 37 publications
13
124
0
Order By: Relevance
“…Reductive Nitrosylation Versus Intermediate Formation, Conformation Dependence-The above results are consistent with preferential binding to ferric heme of NO relative to nitrite under conditions where both are at low concentrations. Ferric NOHb can undergo reductive nitrosylation (13,67,69,89) or, if there is nitrite present, formation of the intermediate that we attribute to heme-bound N 2 O 3 . Because both can be relatively rapid, the question arises as to whether there is a conformational dependence associated with the partitioning of two reactions.…”
Section: Issue Of Mechanistic Sequence No Followed By Nitritementioning
confidence: 89%
“…Reductive Nitrosylation Versus Intermediate Formation, Conformation Dependence-The above results are consistent with preferential binding to ferric heme of NO relative to nitrite under conditions where both are at low concentrations. Ferric NOHb can undergo reductive nitrosylation (13,67,69,89) or, if there is nitrite present, formation of the intermediate that we attribute to heme-bound N 2 O 3 . Because both can be relatively rapid, the question arises as to whether there is a conformational dependence associated with the partitioning of two reactions.…”
Section: Issue Of Mechanistic Sequence No Followed By Nitritementioning
confidence: 89%
“…More recent studies by Fernandez et al demonstrated that the reductive nitrosylations of Fe III (TPPS) [127] and of metHb and metMb [128] are promoted by general base catalysis and by other nucleophiles, including nitrite ion (Scheme 6). In the case of the latter, the catalytic role of nitrite in promoting reductive nitrosylation of these ferric heme models and proteins was first discovered in an attempt to pin down experimental anomalies that were eventually attributed to the ubiquitous NO 2 -impurities in aqueous NO solutions.…”
Section: Reactions Of Iron(iii) Nitrosyls With Nucleophilesmentioning
confidence: 99%
“…Since the Cu(phen) 2 (H 2 O) 2+ analog (phen ¼ 1,10-phenanthroline) is a much weaker oxidant (0.18 V), this property can be attributed to the steric Scheme 6 Proposed mechanism for the nitrite catalysis of the reductive nitrosylation of Fe III (TPPS), metHb, and metMb [127] 122 P.C. Ford et al repulsion between the methyl groups of the respective dmp ligands that favors the tetrahedral coordination of Cu(I) over the tetragonal pyramidal structure of Cu(II).…”
Section: Reduction Of Copper(ii) Complexes By Nomentioning
confidence: 99%
“…The possibility of a similar function has been tested in several hxHbs. In all cases, ferrous hxHbs will bind reversibly to NO [15], the ferric forms will react with NO [74] in some cases showing slow reduction [15,[75][76][77][78], and the oxy-ferrous hxHbs will scavenge NO resulting in their oxidation (Table 3) [75,[79][80][81][82][83]. In spite of the fact that the efficiency of these reactions is at best on-par with Mb and red blood cell Hb, and is certainly limited in vivo by as-of-yet unknown mechanisms for rereduction of the heme iron [4], observation of the NOD reaction has been proposed as support for an NO scavenging function in nsHbs [80,84], Ngbs [79], and Cgbs [85].…”
Section: The Chemistry Of Hexacoordinate Hemoglobinsmentioning
confidence: 99%